(untitled) (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2025)
This article analyzes the norms of civil procedural legislation that regulate the features of evidence in civil proceedings. Particular attention is paid to the means of proof, supported by a complex of judicial practice.